1998
DOI: 10.1002/hep.510270527
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of thymosin ?1 in patients with chronic hepatitis B: A randomized, controlled trial

Abstract: Thymosin ␣ 1 (T␣) is an immune modifier that has been shown in a pilot study to be effective for chronic hepatitis B; this requires confirmation. Ninety-eight patients with clinicopathologically proven chronic hepatitis B were randomly allocated to 3 groups: 1) group A received a 26-week course of T␣ with a 1.6-mg subcutaneous injection two times a week (T 6 group); 2) group B received the same regimen as group A, but T␣ therapy extended for 52 weeks (T 12 group); and 3) group C served as a control group and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 29 publications
(26 reference statements)
7
81
0
2
Order By: Relevance
“…Clinical trials have shown that thymosin is well tolerated but data on efficacy are conflicting. [220][221][222][223] Thus, more studies are needed before thymosin can be recommended for treatment of chronic hepatitis B.…”
Section: Other Therapiesmentioning
confidence: 99%
“…Clinical trials have shown that thymosin is well tolerated but data on efficacy are conflicting. [220][221][222][223] Thus, more studies are needed before thymosin can be recommended for treatment of chronic hepatitis B.…”
Section: Other Therapiesmentioning
confidence: 99%
“…Treatment with thymosin a 1 1.6 mg twice weekly for 6 and 12 months showed a complete response, defined as ALT normalization, undetectable HBV DNA by solution hybridization assay and HBeAg loss at 12 months after the end of therapy in 40-45% and 32% of treated HBeAg-positive patients [66,67]. HBV genotype B responded to therapy better than genotype C (52% vs. 24%, P = 0.036) [67].…”
Section: Thymosin a 1 In Chronic Hepatitis Bmentioning
confidence: 95%
“…The structure of Tai is composed of twenty-eight amino acids and the molecular weight is 3,108. Next Toti has been shown to modulate T-cell function, to promote endogenous IFN-y, and interleukin-2 production by human lymphocytes and to increase lymphocyte interleukin-2 receptor expression (6,22).…”
Section: Clinical Safetymentioning
confidence: 99%
“…However, we found that the efficacy of low-dose (0.8 mg) Toti was not inferior to that of highdose (1.6 mg) Toti. With respect to the total dose of Toti, Chien et al reported that the response rate of patients treated with Toti for 26 weeks was not statistically different from that of patients treated for 52 weeks (6). Toti has pharmacological actions with modulate T-cell function to promote endogenous IFN-y, interleukin-2 production and to stimulate natural killer activity.…”
Section: Clinical Safetymentioning
confidence: 99%
See 1 more Smart Citation